The combination of sorafenib and radiation preferentially inhibits breast cancer stem cells by suppressing HIF-1α expression - LEE, JAE HO (D.A. Spandidos, 2013)
The importance of anticancer stem cell research for breast cancer lies in the possibility of providing new approaches for an improved understanding of anticancer activity and cancer treatment. In this study, we demonstrated that the preclinical therapeutic efficacy of combining the multikinase inhibitor sorafenib with radiation was more effective in hypoxia-exposed breast cancer stem cells. We assessed cell viability and Annexin V to evaluate the combined effect of sorafenib and radiation following exposure to hypoxia. Our results showed that the synergistic cytotoxicity increased tumor cell apoptosis significantly and reduced cell proliferation in MDA-MB-231 and MCF-7 cells under hypoxic conditions compared to sorafenib or radiation alone in vitro. Additionally, the combined treatment induced G2/M cell cycle arrest. Notably, the combination of sorafenib and radiation eliminated CD44(+)CD24(−/low) cells preferentially, which highly expressed hypoxia-inducible factor (HIF)-1α and effectively inhibited primary and secondary mammosphere formation in MDA-MB-231 cells. A combined effect on MDA-MB-231 cells in response to hypoxia was shown by inhibiting angiogenesis and metastasis by suppression of HIF-1α and matrix metalloproteinase-2 (MMP-2). Collectively, these results indicate that the efficacy of sorafenib combined with radiation for treating human breast cancer cells is synergistic and suggest a new therapeutic approach to prevent breast cancer progression by eliminating breast cancer stem cells.